Alpha-synuclein fragments trigger distinct aggregation pathways - Chakroun, Tasnim (Cell Death Dis, 2020)
Aggregation of alpha-synuclein (αSyn) is a crucial event underlying the pathophysiology of synucleinopathies. The existence of various intracellular and extracellular αSyn species, including cleaved αSyn, complicates the quest for an appropriate therapeutic target. Hence, to develop efficient disease-modifying strategies, it is fundamental to achieve a deeper understanding of the relevant spreading and toxic αSyn species. Here, we describe comparative and proof-of-principle approaches to determine the involvement of αSyn fragments in intercellular spreading. We demonstrate that two different αSyn fragments (1–95 and 61–140) fulfill the criteria of spreading species. They efficiently instigate formation of proteinase-K-resistant aggregates from cell-endogenous full-length αSyn, and drive it into different aggregation pathways. The resulting aggregates induce cellular toxicity. Strikingly, these aggregates are only detectable by specific antibodies. Our results suggest that αSyn fragments might be relevant not only for spreading, but also for aggregation-fate determination and differential strain formation.